If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 6 + -9y = 0 Reorder the terms: 6 + 5y + -9y = 0 Combine like terms: 5y + -9y = -4y 6 + -4y = 0 Solving 6 + -4y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -4y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -4y = 0 + -6 -4y = 0 + -6 Combine like terms: 0 + -6 = -6 -4y = -6 Divide each side by '-4'. y = 1.5 Simplifying y = 1.5
| 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= | | Y^2=5Y+50 | | 89=28-r | | 36=-3(-9-3z) | | 33x+117=14.5x | | 6x^3-4x-16x=0 | | 89=21-r | | 12=-8p+11+9p | | 1.5x+10=2x+20 | | 1216=(x*2140)/(7443,8*0,1) | | 2r^2-4=8 | | x^4+5x^2-6= | | -7x+17= | | 2875=(x*2140)/(4008,2*0,1) | | 3q+4p=12 | | 1/2z=-3/4+1/4z | | 9x-11=5x-9 | | 5y-7x=11 | | X^2-8x-161=0 | | -5+(-4x)=-53 |